Survey of the family Russulaceae (Agaricomycetes, Fungi) in Montenegro - Kasom, Gordana; Karadelev, Mitko (Acta Botanica Croatica, 2012)
The paper shows that there are 84 known species of the family Russulaceae in Montenegro, 39 of them belonging to the genus Lactarius and 45 to the genus Russula.